Mechanical properties of three-phase polyamide 6 nanocomposites - Gendre, Laura; Abhyankar, Hrushikesh; Njuguna, James; Ermini, Valentina (Cranfield University Press, 2013)
This work focus on the mechanical properties of three-phase nanocomposites using multiscale reinforcements. The influence of the nano-fillers content, as well as the temperature were studied. Polyamide-6 reinforced with short glass fibre 30 wt.% and with an addition of nanoclay (montmorillonite) and/or nanosilica (SiO2) were tested in order to characterise their tensile properties at room temperature and at 65oC just above the polyamide 6 glass transition temperature. SEM analysis were conducted on the fracture surface of the tensile bars. SEM investigations showed the importance of the interaction matrix/filler for the material behaviour. Our study also shows that the increase of OMMT percentage in polyamide-6/glass fibre composite made the material more brittle and had a negative effect on the tensile properties. Further, for the silica-based nanocomposites, an optimum was found for a nanofillers content of 1wt.%.
Keywords: Three-Phase Nanocomposites; Polyamide-6; Impact